PRINCIPLES OF WORLD TRADE LAW - Collins, David, 1975- (ROUTLEDGE, 2025)
"Principles of World Trade Law presents a comprehensive and balanced picture of the legal framework underpinning the modern world trading system - covering the law of the WTO but also drawing on bilateral and regional instruments. It acknowledges the shifting relevance of the WTO in world trade law in favour of regionalism, particularly in relation to new fields such as digital trade. While drawing heavily on the law of the WTO as a source of legal rules, this concise text also engages with elements found in preferential Free Trade Agreements (FTAs) (such as Rules of Origin) and mutual recognition agreements (such as recognition of professional qualifications in the case of services). Practical in nature, it blends straightforward descriptive explanation of the legal concepts with critical inquiry, directing readers to the key debates in the field as well as the source materials themselves. It also offers guidance with discussion questions for the reader to consider for each chapter. Principles of World Trade Law is an ideal introductory textbook for advanced undergraduate and postgraduate students taking courses in world trade law, international trade law and international economic law, as well as a valuable guide for scholars, legal practitioners and policymakers"--